High incidence of lichen sclerosus in patients with squamous cell carcinoma of the penis. - Powell, J; Robson, A; Cranston, D; Wojnarowska, F; Turner, R (2001)
BACKGROUND: There is a well-documented association between lichen sclerosus (LS) and vulval carcinoma in women; however, until recently, there have only been anecdotal reports of penile squamous cell carcinoma (SCC) occurring in men with LS. OBJECTIVE: The incidence of penile carcinoma occurring on a background of LS remains uncertain, and we wished to examine this possible association further. METHOD: To address this, all the cases (n = 20) of penile SCC held on our pathology database (4 years) were examined. Histology was reviewed, blind to the clinical picture, for evidence of LS, applying strict histological criteria. Subsequently, clinical notes were reviewed for history of LS before the SCC presented, and history of previous circumcision, treatments, node involvement, metastases and death. RESULTS: In eight cases, evidence of LS was found in the excision specimen. Seven of these had well-differentiated SCC. In the 12 cases with no evidence of LS, only three were well differentiated. With case note review, seven had a history of LS (four with histological LS), sometimes preceding the SCC by 10 years. These all had well-differentiated SCC. Ten of the 20 patients are dead, seven from metastatic disease. Four deaths occurred in the 'well-differentiated LS' group, but only one from penile SCC metastatic disease. CONCLUSIONS: There appears to be a definite association between SCC of the penis and the presence of LS, similar to that reported between LS and vulval SCC in women. Of the 20 patients with penile SCC studied, 11 had a clinical history and/or histological evidence of LS. However, clinical presentation of the LS or need for circumcision may precede the SCC by many years. As follow-up is impractical, counselling at the time of diagnosis is very important, and it is essential that medical practitioners are aware of this association so that the subsequent risk from SCC is reduced.